2012
DOI: 10.1016/j.ajhg.2012.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Exome Sequencing and Functional Validation in Zebrafish Identify GTDC2 Mutations as a Cause of Walker-Warburg Syndrome

Abstract: Whole-exome sequencing (WES), which analyzes the coding sequence of most annotated genes in the human genome, is an ideal approach to studying fully penetrant autosomal-recessive diseases, and it has been very powerful in identifying disease-causing mutations even when enrollment of affected individuals is limited by reduced survival. In this study, we combined WES with homozygosity analysis of consanguineous pedigrees, which are informative even when a single affected individual is available, to identify gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
96
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(100 citation statements)
references
References 29 publications
3
96
0
1
Order By: Relevance
“…Mutant mice of the integrin-related family, such as FAK (focal adhesion kinase) [233] and Ilk (integrin-linked kinase) [235], have been associated with features that resemble human COB-LIS, including cortical migration and basal lamina integrity defects, but mutations of these genes have not been identified in human patients.…”
Section: Fkrp-neomentioning
confidence: 99%
“…Mutant mice of the integrin-related family, such as FAK (focal adhesion kinase) [233] and Ilk (integrin-linked kinase) [235], have been associated with features that resemble human COB-LIS, including cortical migration and basal lamina integrity defects, but mutations of these genes have not been identified in human patients.…”
Section: Fkrp-neomentioning
confidence: 99%
“…Il est également impliqué dans des cas de LISII foetale [2]. Le gène GTDC2 est, pour sa part, impliqué dans des formes de LISII sévères, dans des cas de WWS post-natal ou des formes moins sévères de LGMD [19]. Enfin, un cinquième gène, B3GALNT2, code une glycosyltransférase du réticulum endoplasmique.…”
Section: Gènes Associés Aux Alpha-dystroglycanopathiesunclassified
“…Defects in this gene are seen in patients presenting with Walker-Warburg syndrome, and knockdown of this gene in zebrafish recapitulated the phenotype of the knockdown of POMT1 (75). It was speculated that this enzyme might be a xylosyltransferase (GT61 does contain ␤1,2-xylosyltransferases) (75). Sequence comparison showed that this enzyme also has high homology to the recently described secretory pathway-localized protein O-␤-N-acetylglucosaminyltransferase (EGF domain-specific O-GlcNAc transferase) (76,77).…”
Section: -C-methyl-d-erythritol 4-phosphate Cytidylyltransferaselikementioning
confidence: 99%
“…This glycosyltransferase belongs to the CAZy inverting GT61 family. Defects in this gene are seen in patients presenting with Walker-Warburg syndrome, and knockdown of this gene in zebrafish recapitulated the phenotype of the knockdown of POMT1 (75). It was speculated that this enzyme might be a xylosyltransferase (GT61 does contain ␤1,2-xylosyltransferases) (75).…”
Section: -C-methyl-d-erythritol 4-phosphate Cytidylyltransferaselikementioning
confidence: 99%
See 1 more Smart Citation